2012
DOI: 10.1210/jc.2011-2134
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Reference Ranges for Serum Testosterone and Androstenedione Concentrations in Women Measured by Liquid Chromatography-Tandem Mass Spectrometry

Abstract: This is the first study to establish age-specific reference ranges for liquid chromatography-tandem mass spectrometry-measured TT and AD and calculated free T concentrations based on quantile regression analyses, accurately accounting for the observed low concentration range and the strong age dependency of these sex hormones in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
94
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 37 publications
15
94
1
3
Order By: Relevance
“…Therefore only women who had not used hormonal contraception for at least 3 months were included in the study and there was a 3-cycle run-in period with COC use alone prior to the DHEA/placebo treatment period. The observed qualitative changes of the (precursor) androgens and SHBG after COC use alone are in agreement with previous studies [1,2,[17][18][19][20][21], but the quantitative suppression of total T and free T by 62% and 86%, respectively is more pronounced than reported in the literature previously (mean of 31% and 61%, respectively) [1]. Importantly, all COC users experienced a decrease of their total and free T.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore only women who had not used hormonal contraception for at least 3 months were included in the study and there was a 3-cycle run-in period with COC use alone prior to the DHEA/placebo treatment period. The observed qualitative changes of the (precursor) androgens and SHBG after COC use alone are in agreement with previous studies [1,2,[17][18][19][20][21], but the quantitative suppression of total T and free T by 62% and 86%, respectively is more pronounced than reported in the literature previously (mean of 31% and 61%, respectively) [1]. Importantly, all COC users experienced a decrease of their total and free T.…”
Section: Discussionsupporting
confidence: 92%
“…6 In cross-sectional studies, concentrations of total testosterone have been reported to be lower in postmenopausal compared with premenopausal women, 7,8 whereas in longitudinal studies, either no change 9 or a 15% to 30% fall have been reported. 10,11 In the present study of women from the general population, we observed the expected fall in estradiol coinciding with menopause, whereas testosterone concentrations were largely unchanged from the age of 20 to >80 years.Median plasma estradiol and testosterone concentrations were in the present study relatively high in both pre-and postmenopausal women. The reason for this is unknown; however, Figure 2.…”
supporting
confidence: 44%
“…Although normal androgen cut-off levels have not been precisely established for menopause, it is generally accepted that they do not exceed those of premenopausal women (6,13). However, androgen levels are consistently higher in patients with nontumorous hyperandrogenism compared with nonhyperandrogenic postmenopausal women (14,15).…”
Section: Causes Of Hyperandrogenism After Menopausementioning
confidence: 99%
“…This state of relative androgen excess is biochemically best identified with the measurement of serum testosterone levels that only rarely exceed those found in premenopause (i.e. !40 ng/dl or 1.38 nmol/l) (6). After menopause, even such testosterone levels may lead to the development or re-appearance of hyperandrogenic symptoms clinically evident mainly in the skin as the appearance of a few terminal hairs in the face and decrease in body and scalp hair (7).…”
Section: Introductionmentioning
confidence: 99%